KUALITAS TELUR AYAM ARAB KONSUMSI DAN PERUBAHAN MUTUNYA SELAMA PENYIMPANAN PADA SUHU YANG BERBEDA (Quality Changes of Arabian Chicken Table Eggs During Storage at Different Temperatures) - Herwin Pisestyani; Erlangga Putra Wijaya; Ekowati Handharyani; Denny Widaya Lukman (Universitas Nusa Cendana, 2026)
The quality of Arabic Chicken table eggs (Gallus turcicus) and changes in quality during storage at room temperature (25–27 °C) and refrigerated temperature (4–7 °C) were evaluated. A total of 200 fresh eggs obtained from Arabic laying hens at peak production (30–40 weeks of age) were assigned to two storage temperature groups. Measurements were performed on days 0, 5, 10, 15, 20, 25, 30, 35, 40, and 45, using five eggs per group at each sampling time. External quality (egg weight and air cell height) and internal quality (yolk index, albumen index, and Haugh Unit) parameters were determined. Data were analyzed using two-way analysis of variance (ANOVA) to assess the effects of storage temperature, storage duration, and their interaction, followed by Tukey's post hoc test. Storage temperature, storage duration, and their interaction were found to have significant effects (P < 0.05) on air cell height, yolk index, and Haugh Unit. A significant temperature–time interaction indicated that the rate of egg quality deterioration depended on both storage temperature and storage duration. Eggs stored at room temperature exhibited faster quality deterioration, which was detected as early as day 10 of storage, as evidenced by decreased yolk index and Haugh Unit values and increased air cell height. In contrast, eggs stored under refrigerated conditions showed greater stability, with internal quality maintained until days 40–45 of storage. Overall, refrigerated storage was more effective than room-temperature storage in maintaining the quality of Arabic chicken table eggs.